A preliminary study of antibiotics resistance in wastewater treatment plants - Selvaraju, Kausalyah; Lee, Chin Mei; Tay, Joo Hui; Khaw, Kooi Yeong; Nurul `Azyyati, Sabri (AIP Publishing, 2025)
Antibiotics have been widely consumed by humans and animals to treat infections and diseases caused by bacteria. However, long-term consumption of antibiotics has contributed to antibiotic resistance in the environment including wastewater treatment plants (WWTPs). The WWTPs have been identified as an important reservoir and a point source for antibiotic resistance released into the environment. The main objective of this study was to detect the presence of antibiotics and other physicochemical parameters in a municipal WWTP and a hospital WWTP in Kuantan District, Pahang. Various physicochemical parameters such as pH, temperature, dissolved oxygen, chemical and biological oxygen demand, and total phosphate were measured, and the presence of antibiotics was analyzed by Liquid chromatography quadrupole time-of-flight mass spectrometry (LC-QToF-MS). Some physicochemical parameters of the effluent exceeded the Malaysian Standard B. Aminoglycoside, macrolides, beta-lactams, tetracyclines, and trimethoprim were detected in the effluent of the municipal and hospital WWTP. This study would provide baseline data on antibiotics as pollutants in WWTPs. particularly in the Kuantan District and would embark on future research such as detecting antibiotic-resistant bacteria and antibiotic-resistance genes.